'Plain vanilla' banking? The financialization of Spanish regional savings banks. Issue 1 (1st January 2017) - Portas, Paula
Abstract: Dominant narratives of the sovereign debt crisis in Spain blamed regional savings bank's old-style lending patterns and naïve management for creating a 'traditional' banking crisis which eventually caused their own demise. Yet these narratives rest on an over-territorialized representation of regional finance. This article offers a regionally sensitive narrative of the conditions of possibility of the banking crisis in Spanish SBs by tracing the history of their deregulation and, using Catalonia as an exemplary case, their progressive financialization. Hence, it provides an alternative explanation of how savings banks came to be at the centre of the financial crisis in Spain, one that stresses the relevance of the interconnectivities between regional financial communities and the European financial market.